Mortality in patients with isolated congenital complete atrioventricular block in Sweden: a register-based, nationwide cohort study. (14th October 2021) - Shao, Y; Kok, W; Eriksson, P; Johansson, B; Dellborg, M; Mandalenakis, Z
Abstract: Purpose: The congenital heart block is a rare but potentially serious heart conduction disease and associated with high mortality during the fetal or neonatal periods. Earlier reports are based on relatively small number of patients and there are limited data about long-term outcomes. Methods: Data were collected from the Swedish Patient and Cause of Death register to identify all patients who were born and diagnosed with isolated congenital complete atrioventricular block (CCAVB) between 1970 and 2017. Each patient with isolated CCAVB was matched with 10 control individuals, by birth year and sex from the Total Population Register. Results: Totally 506 patients with CCAVB and 5, 050 controls included in the study (55.3% males). The incidence rate of mortality in patients with isolated CCAVB was 166 per 10.000 person-years. The overall risk of mortality in patients with isolated CCAVB was 45.4 times (95% confidence interval (CI) 32.7–62.9) higher compared to matched controls. In a subgroup investigation, the highest risk of mortality was found in patients with isolated CCAVB from birth until the age of 17 (hazard ratio 80.8, 95% CI 51.6–126.4), compared to matched controls without CCAVB. Conclusion: In this nationwide cohort study, patients with isolated CCAVB was associated with more than 40-fold risk for overall mortality compared to age and sex matched controls. The greatest risk was found during childhood. Regularly follow-up in tertiary centers and the aware of high risk of complications may be the key to prevention. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The Swedish Government, the Swedish Research Council